The Urgency of Asbabun Nuzul in Understanding the Context of the Qur'an Verses - Suci Handayani; Nur Efendi; Qomarul Huda (ALSYS, 2026)
Asbāb al-nuzūl, as a discipline within Ulūm al-Qur’an, provides an essential framework for connecting Qur’anic verses with the historical, social, and situational contexts in which they were revealed. This study aims to analyze the concept, classification, wisdom, and urgency of asbāb al-nuzūl in contemporary tafsir studies. Employing a qualitative literature-based approach, the study draws on primary sources from Qur’anic sciences and secondary sources from scholarly journal articles. Data were collected through documentation and analyzed using a descriptive-analytical method. The findings indicate that, both etymologically and terminologically, asbāb al-nuzūl refers to events, questions, or conditions that served as the background for the revelation of Qur’anic verses. Its main classifications consist of multiple causes for a single revelation (ta‘addud al-asbāb wa al-nāzil wāḥid) and a single cause for multiple revelations (ta‘addud al-nāzil wa al-asbāb wāḥid), reflecting the dynamic nature of revelation in responding to diverse social needs. The study further shows that understanding asbāb al-nuzūl offers practical benefits, including clarifying the meaning of verses, determining the scope of legal application, preventing misinterpretation, and strengthening memorization and contextual comprehension. Its urgency has become increasingly significant in the contemporary era, particularly in preventing disproportionate literal readings and supporting the contextual application of Qur’anic teachings. The study concludes that strengthening the study of asbāb al-nuzūl is crucial for developing an accurate, relevant, and contextually grounded methodology for interpreting the Qur’an in response to modern challenges.